Mercury biogeochemistry over the Tibetan Plateau: An overview. Issue 6 (1st March 2021) - Sun, Ruiyang; Sun, Guangyi; Kwon, Sae Yun; Feng, Xinbin; Kang, Shichang; Zhang, Qianggong; Huang, Jie; Yin, Runsheng
Abstract: Since the beginning of the 21st century, our knowledge of the sources and fate of Hg over the Tibetan Plateau (TP), the "Roof of the World, " has been greatly enhanced with growing literature. Here, we reviewed the available literature to obtain a comprehensive understanding of Hg biogeochemistry over the TP. The biogeochemical Hg cycling is characterized by the following features: (1) There are existing but limited local emission sources of anthropogenic Hg in the TP. The Indian Summer Monsoon is an important transporter of atmospheric Hg pollution into the inland TP; (2) "Cold trapping effect" plays an important role in the atmospheric Hg deposition over the TP. Glacier, vegetation, and soil act as important "sinks" of atmospheric Hg pollution; (3) Enhanced anthropogenic activities around the TP, climate warming and glacier melting have the potential impacts to affect the behavior and distribution of Hg; (4) Significant bioaccumulation of MeHg (>100 ng/g) has been found in the Tibetan aquatic food chains. Considering that transboundary transport is responsible for the widespread Hg pollution in the TP, international/regional collaborations regarding Hg emission regulations are needed to reduce the migration of Hg and to mitigate adverse Hg pollution impacts on the TP. Abstract : UF0001